LIGHT EXPOSURE’S EFFECTS ON INACTIVE STATE DURATION AND SLEEP LATENCY IN ZEBRAFISH (DANIO RERIO) LARVAE INSOMNIA MODEL - Zamroni Afif; Mochammad Istiadjid Eddy Santoso; Husnul Khotimah; Irawan Satriotomo; Edi Widjajanto; Masruroh Rahayu; Shahdevi Nandar Kurniawan; Dheka Sapti Iskandar; Annisatul Hakimah; Syafiatul Azizah; Nurvia Andriani; Kartika Agustina (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2022)
Background: Insomnia is defined as difficulty falling or staying asleep or a sleep state that cannot restore the body's condition. The zebrafish (Danio rerio) is a vertebrate model that has been extensively studied to study sleep and neurological disorders. One of the most widely used methods to examine the effect of the light-dark cycle on the circadian system is by exposing animals and humans to pulse wave light. Objective: To see the effect of light exposure on zebrafish larvae by looking at inactive state duration and sleep latency in zebrafish (Danio rerio) larvae insomnia model. Methods: This study used four groups of zebrafish larvae i.e : (1) normal group (2) minutes of light exposure and 2 minutes off (2/2)), (3) Four minutes of light exposure and 1 minute off (4/1), and (4) 24 hours on (24/0). Observation of larval movement was carried out on 5, 6, and 7 dpf (day post fertilization). Observation time was 30 minutes before and after turned off of light exposure. Results: There were significant differences on days 5, 6, and 7 between the normal group and the three light treatment groups on inactive state duration and sleep latency in dark and light conditions with p-values (p<0.05) and (p< 0.031), but there was no significant difference among groups of light exposure 2 minutes on 2 minutes off, 4 minutes on 1 minute off, and 24 hours on. The 24-hour on treatment showed the most inactive state duration among the light treatments, while the sleep latency was found in the 24-hour treatment. Conclusion: Light treatment of 2 minutes on 2 minutes off, 4 minutes on 1 minute off, and 24 hours on can cause insomnia, but the most substantial insomnia effect is obtained from the 24-hour treatment.